Absence of human papillomavirus genomic sequences detected by the polymerase chain reaction in oesophageal and gastric carcinomas in Japan. Issue 2 (April 1997) - Saegusa, M; Hashimura, M; Takano, Y; Ohbu, M; Okayasu, I
Abstract : AIMS: To estimate the occurrence of human papillomavirus (HPV) infection in oesophageal or gastric carcinomas in patients in Japan. METHODS: 103 oesophageal and 99 gastric carcinomas were investigated by polymerase chain reaction (PCR) assays using two consensus (targeting either the L1 or the E6-E7 regions) and two type specific (type 16 and 18) primer sets. A beta globin gene specific primer set was also applied to examine the quality of the extracted DNA. RESULTS: Amplification of beta globin gene was clearly visible in 92 (89.3%) of the 103 oesophageal, and 89 (89.8%) of the 99 gastric carcinoma specimens. However, the entire series of tumour DNA was negative for HPV sequences by PCR assay using all four primer sets. CONCLUSION: HPV is not likely to be involved in oesophageal or gastric tumorigenesis in Japanese patients.